تقدير مستوى رضا المرضى عن الخدمات الصحية التي تقدمها المستشفيات الحكومية في الساحل السوري دراسة ميدانية - العلي, إبراهيم; دريباتي, يسيرة; أحمد, وسيم (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The aim of the research is to identify the level of patient satisfaction with the health services provided by the governmental hospitals in the Syrian coast, whether with respect to the doctors treating them, the nursing staff, or the level of service and organization. The research was based on the descriptive approach and the survey method. The questionnaire was used as the main source of data and information. The research community consisted of patients residing in government hospitals in Latakia and Tartous, where 425 questionnaires were distributed to patients, 400 of which were complete and valid for statistical analysis, with a response rate of 94.12%. The research reached a number of results, the most important of which are: * Satisfaction of patients with doctors treated in public hospitals in the Syrian coast is good, with a relative importance (64.684%). *The satisfaction of patients with nursing staff in general in public hospitals in the Syrian coast was of medium level, with a relative importance (64.556%). *Patients' satisfaction with service and organization in general in the public hospitals in the Syrian coast was of medium level, with relative importance (63.51%). *Patients' satisfaction with the quality of treatment provided in public hospitals in the Syrian coast was of medium level and relative importance (65.9%). *Patients' satisfaction with the quality of services provided in public hospitals in the Syrian coast was of medium level and relative importance (65.6%). يهدف البحث إلى التعرف على مستوى رضا المرضى عن الخدمات الصحية التي تقدمها المستشفيات الحكومية في الساحل السوري, سواء ما يتعلق بالأطباء المعالجين, أو ما يتعلق بالكادر التمريضي, أو ما يتعلق بمستوى الخدمة والتنظيم. اعتمد البحث على المنهج الوصفي, وأسلوب المسح, حيث اُستخدمت الاستبانة كمصدر رئيس في الحصول على البيانات والمعلومات. وتكوّن مجتمع البحث من المرضى المقيمين في المستشفيات الحكومية في مدينتي اللاذقية وطرطوس, حيث تمّ توزيع (425) استبانة على المرضى, وأعيد منها (400) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (94.12%). توصل البحث إلى مجموعة من النتائج أهمها: * إنّ رضا المرضى عن الأطباء المعالجين بشكل عام في المستشفيات الحكومية في الساحل السوري كان من المستوى المتوسط, وبأهمية نسبية (64.684%). * إنّ رضا المرضى عن الكادر التمريضي بشكل عام في المستشفيات الحكومية في الساحل السوري كان من المستوى المتوسط, وبأهمية نسبية (64.556%). * إنّ رضا المرضى عن الخدمة والتنظيم بشكل عام في أقسام المستشفيات الحكومية في الساحل السوري كان من المستوى المتوسط, وبأهمية نسبية (63.51%). * إنّ رضا المرضى عن جودة العلاج المقدم بشكل عام في المستشفيات الحكومية في الساحل السوري كان من المستوى المتوسط, وبأهمية نسبية (65.9%). * إنّ رضا المرضى عن جودة الخدمات المقدمة بشكل عام في المستشفيات الحكومية في الساحل السوري كان من المستوى المتوسط, وبأهمية نسبية (65.6%).